MAIN ASPECTS OF DETERMINING THE STATE OF EXTRACURRICULAR WORK ON THE FORMATION OF COMMUNICATIVE CULTURE OF STUDENTS IN THE PRACTICE OF HIGHER PEDAGOGICAL (Pedagogy of Higher and Secondary Education, 2010)
The article deals with the analysis of the slate of extra-curriculum activity in the process of higher pedagogical school and causes of low level of students' communicative culture.
Keywords: extra-curriculum activity; communicative culture; higher pedagogical school